1999
DOI: 10.3354/meps180139
|View full text |Cite
|
Sign up to set email alerts
|

In situ underwater measurements of photosynthetic activity of coral zooxanthellae and other reef-dwelling dinoflagellate endosymbionts

Abstract: Chlorophyll fluorescence was used to assess the in situ photosynthesis of a range of reefdwelling endosymblonts. Such non-intrusive in situ measurements became possible after the recent development of a submersible pulse modulated fluorometer (DIVING-PAM, Walz, Germany). Several corals, a clam ( T~d a c n a maxima) and an anemone (Heteractis sp.) all showed strong chlorophyll a fluorescence signals originating from the dinoflagellate endosymbionts. Quenching analysis by the saturation pulse method revealed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 20 publications
6
84
2
Order By: Relevance
“…The second, chronic photoinhibition is associated with much more severe damage to PSII, recovers extremely slowly, and is interpreted as photon damage. Although dynamic photoinhibition occurs widely in phytoplankton , macroalgae (Hanelt et al 1993;Franklin et al 1996), and corals (Brown et al 1999;Hoegh-Guldberg and Jones 1999;Ralph et al 1999; this study), signs of chronic photodamage have previously been observed only in corals exposed to elevated temperatures (Jones et al 1998;Warner et al 1999) or intertidal corals under solar bleaching (Brown et al 2000). Our data on a number of shallow corals clearly suggest that the daily exposure to full sunlight leads to chronic photoinhibition, even at moderate temperatures (24-29ЊC).…”
Section: Discussionmentioning
confidence: 97%
“…The second, chronic photoinhibition is associated with much more severe damage to PSII, recovers extremely slowly, and is interpreted as photon damage. Although dynamic photoinhibition occurs widely in phytoplankton , macroalgae (Hanelt et al 1993;Franklin et al 1996), and corals (Brown et al 1999;Hoegh-Guldberg and Jones 1999;Ralph et al 1999; this study), signs of chronic photodamage have previously been observed only in corals exposed to elevated temperatures (Jones et al 1998;Warner et al 1999) or intertidal corals under solar bleaching (Brown et al 2000). Our data on a number of shallow corals clearly suggest that the daily exposure to full sunlight leads to chronic photoinhibition, even at moderate temperatures (24-29ЊC).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, those studies were not performed in situ, but on corals held in aquariums, which might have been further stressed by the methods of dark adaptation used prior to the measurements. Using the last data point of rapid light curves performed in situ for several species at different times of the day, Ralph et al (1999) found similar midday depressions in maximum ETR and explained this also to be dynamic photoinhibition. In contrast to the above studies, the measurements in our study were performed in situ and under natural irradiances (without dark adaptations).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the Diving-PAM, measurements of chlorophyll fluorescence became applicable also for in situ research of coral photosynthesis (Beer et al 1998;Ralph et al 1999). However, those in situ works did not make use of the ambient irradiance during the measurements.…”
mentioning
confidence: 99%
“…) in the form of a rapid light curve (RALPH et al, 1999;GADEMANN, 2005). Light-adapted fluorescence yield (F s ) and maximum light-adapted fluorescence yield (F' m ) were determined at the end of a 10 sec period at each irradiance level, and the effective quantum yield of PSII as a function of irradiance was calculated from…”
Section: Biological Materialsmentioning
confidence: 99%